Pengaruh Profitabilitas Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak Pada Perusahaan Food And Beverage Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Elvira, Bella; Siregar, Akbar; Dalimunthe, Hasbiana (Universitas Medan Area, 2022)
This research aimed to analyze the effect of profitability and sales growth against tax avoidance. Measurement of tax avoidance in this research is used Effective Tax Rate (ETR). The population in this research is the Food and Beverage companies listed in Indonesia Stock Exchange in 2015-2019. The data used in this research is a secondary data obtained from www.idx.co.id. The selected sample were 9 companies obtained by purposive sampling method. The data analysis method in this research are descriptive statistics, multiple linear regression analysis, classic assumption tests, and hypothesis testing using Software Statistical Product and Service Solution (SPSS) ver. 23. The results of this research showed that profitability and sales growth has a negative and significant effect on tax avoidance. This means if profitability and sales growth is increase then tax avoidance will decrease.slot gacor